Cognitive Load, Ego Depletion, dan Epistemic Agency dalam Interaksi Mahasiswa dengan ChatGPT: Bukti Awal dari Studi Eksperimental - M. Agung Lyndardi; Riyanto; Cleoputri Yusainy (Buletin Riset Psikologi dan Kesehatan Mental, 2026)
The use of generative AI in academic learning may diminish students’ epistemic agency, particularly under high cognitive load. This within-subject experiment examined the causal effect of cognitive load on epistemic agency during ChatGPT-assisted tasks and the role of ego depletion. Thirty-six undergraduate students completed tasks of varying complexity. Epistemic agency was assessed through behavioral coding across three dimensions (initiative, regulation, and evaluation; ICC = .941–.984), while ego depletion was measured using a Stroop task. Results showed that cognitive load significantly reduced epistemic agency with a large effect size (t(35) = 9.736, p < .001, d = 1.62). The mediation hypothesis was not supported (indirect effect = .004, 95% CI [−.069, .048]). However, exploratory post-hoc analyses indicated that ego depletion moderated this relationship (b = −.005, p = .039), with higher self-regulatory depletion amplifying the negative effect of cognitive load on epistemic agency.